Evaluasi Kerjasama Sinode Gereja Isa Almasih dan Sinode Gereja Presbiterian Korea Selatan - Choi Yong Sung (JURNAL LUXNOS, 2021)
Abstract: 2021 is a Jubellium year of Presbyterian Korean Missionary came to Indonesia. For human, 50th is a sign of mature. There are many experiences in 50th years journey of Korean mission in Indonesia. But of course, it has not been a smooth journey. We came to Indonesia with the idea of partnership mission with local Church. But many of the partnership ended by conflict. GIA is one of the good model of success mission partnership of Korea and Indonesia. Of course, this partnership mission is not a smooth mission too. This article wrote by field research through interview with many experienced interviewees from Korean Missionary especially Presbyterian Church of Korea and The Local Leader Church of Gereja Isa Almasih (GIA). Hopefully this article can give many of missionary and Indonesia local leader a very well model of partnership mission. Abstrak: Tahun 2021 merupakan tahun Jubelium Presbyterian Korean Missionary datang ke Indonesia. Bagi manusia, usia ke-50 adalah tanda kedewasaan. Ada banyak pengalaman dalam 50 tahun perjalanan misi Korea di Indonesia. Tapi tentu saja, ini bukanlah perjalanan yang mulus. Kami datang ke Indonesia dengan ide misi kemitraan dengan Gereja lokal. Tetapi banyak dari kemitraan itu berakhir dengan konflik. GIA adalah salah satu model sukses misi kemitraan Korea dan Indonesia. Tentunya misi kemitraan ini juga bukan misi yang mulus. Artikel ini ditulis berdasarkan penelitian lapangan melalui wawancara dengan banyak narasumber berpengalaman dari Korean Missionary khususnya Presbyterian Church of Korea dan The Local Leader Church of Gereja Isa Almasih (GIA). Semoga artikel ini dapat memberikan model bagi banyak misionaris dan pemimpin lokal Indonesia tentang misi kemitraan.